Islamisasi Pendidikan di Indonesia Melalui Pendidikan Islam - Nizam Zulfa; Haifani Hilal (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article examines the history and development of the Islamization of education in Indonesia. This study aims to analyse Islamisation of education through Islamic education by looking at historical data that shape the patterns and characteristics of Islamic education in Indonesia, as well as identifying critical points that influence the direction of its development. The research uses the theory of historical institutionalism. Through a literature study with a qualitative approach, the research reveals that the development of Islamic education in Indonesia followed a strong path dependence pattern, where decisions in the colonial and early independence periods shaped a relatively stable institutional path. The findings show that the process of educational Islamization underwent institutional layering, where new elements were added without completely erasing the old structure. This research contributes to the theoretical understanding of the dynamics of institutional change in the context of Islamic education in Indonesia.